Analyzing Technology Acceptance Model for Lombok Traditional Food Restaurant in GoFood Application - Bimantari, Joselina Rizki; Alamsyah, Noor; Murpratiwi, Santi Ika (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
During the COVID-19 pandemic, Lombok Island, known for its stunning natural beauty, faced significant challenges in its culinary industry, resulting in a drastic decline in revenue and tourist visits. Embracing technological solutions, particularly through food delivery apps like GoFood, became pivotal in overcoming these obstacles. These apps not only sustained local restaurants during the pandemic but also preserved Lombok's distinctive cuisine, such as Sate Rembiga. Beyond pandemic resilience, GoFood played a crucial role in balancing global technological advancements and supporting daily activities. The aim of this research is to employ the Technology Acceptance Model (TAM) using Partial Least Square (PLS) approach to analyze the adoption of the GoFood application among owners of traditional Lombok cuisine restaurants, particularly focusing on the impact of the COVID-19 pandemic. This research method is designed to assess the extent of acceptance and adoption of GoFood among these restaurant owners during the pandemic, identifying key factors influencing their technological acceptance. The results of this research offer insights into the dynamics of technology acceptance within Lombok's culinary sector amid external changes such as the pandemic. In conclusion, understanding these dynamics can inform strategies to enhance the utilization of food delivery apps in traditional culinary businesses, ensuring resilience and adaptation in the face of unforeseen challenges.